Moral Values in the Novel “Pasta Kacang Merah” By Durian Sukegawa: A Literary Sociology Approach - Pinta Ria Saragih; Ikhwanuddin Nasution; Nurhayati Harahap (International Journal of Education, Information Technology, and Others, 2026)
This study aims to describe the moral values ​​contained in the novel "Pasta Kacang Merah" by Durian Sukegawa using a sociology of literature approach. The moral values ​​analyzed include the relationship between humans and themselves, the relationship between humans and others, and the relationship between humans and God. The method used in this study is a qualitative descriptive method with content analysis techniques on relevant quotations from the novel. The results of the study show that this novel is full of moral values, such as an attitude of gratitude, discipline, patience, and humility which are reflected in the relationship between humans and themselves. In relationships with others, the values ​​of empathy, tolerance, solidarity, and respect for others are found. Meanwhile, the relationship between humans and God is seen through spiritual awareness, an attitude of surrender, and gratitude for life. The moral values ​​contained in this novel not only enrich the character of the characters, but also provide valuable lessons for readers about the importance of building good character and maintaining harmonious relationships with others and God. This research is expected to contribute to the development of literary studies, especially in understanding the role of literary works as a medium for character formation and instilling moral values.